STRATA SOSIAL MASYARAKAT JAWA SEBAGAI BAHASA NONVERBAL STATIS : KAJIAN ETNOPRAGMATIK - Pranowo Pranowo; Ratna Susanti (Aksara, 2020)
Artikel ini membahas strata sosial masyarakat Jawa sebagai bahasa nonverbal statis yang dikaji secara etnopragmatik. Kajian ini merupakan kajian interdisipliner antara teori etnografi dan pragmatik. Teori etnografi adalah kajian yang menggambarkan budaya suatu masyarakat, sedangkan kajian pragmatik pada dasarnya menggambarkan penggunaan bahasa berdasarkan konteks. Dengan demikian, kajian etnopragmatik adalah kajian penggunaan bahasa berdasarkan konteks budaya masyarakat pemiliknya. Tujuan penelitian adalah menggambarkan wujud, fungsi, dan makna pragmatik yang terdapat dalam strata sosial masyarakat Jawa. Desain yang digunakan dalam penelitian adalah deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan perekaman. Analisis data dilakukan melalui langkah konkret (a) identifikasi data, (b) klasifikasi data, dan (c) interpretasi data. Temuan hasil penelitian berupa (a) strata sosial tingkat kepriyayian, (b) strata sosial kedudukan seseorang di dalam masyarakat, (c) strata sosial yang diungkapkan secara metaforis, (d) strata sosial dalam memilih jodoh, (e) strata sosial temu trah, dan (d) strata sosial bias gender.This article aims to identify the social strata of Javanese society as a static nonverbal language that is studied ethnopragmatically. This study is an interdisciplinary study of ethnographic and pragmatic theories. The theory of ethnography is a study that describes the culture of a society, while pragmatic studies basically describe the use of language based on context. Thus, ethnopragmatics review is the study of language use based on the cultural context of the owner’s community. The purpose of this study is to describe the form, function, and pragmatic meaning contained in the social strata of Javanese society. The design used in this research is descriptive qualitative. Data collection techniques used were observation, interviews, and recording. The data collection techniques used were carried out for two months (January-February 2020) by recording public speech in the Sleman area of Yogyakarta as a random sampling informant Data analysis was performed through concrete steps, namely: (a) data identification, (b) data classification, and (c) data interpretation. Data validity test was used data triangulation techniques, namely data triangulation and theory’s triangulation. The findings of the research are (a) social strata at the community level, (b) social strata of a person’s position in society, (c) social strata expressed metaphorically, (d) social strata in choosing a mate, (e) social layers of meeting, and (d) social strata of gender bias. Keywords: nonverbal language, ethnopragmatics, social level